Improving English Vocabulary Using Visual Mnemonic Technique - Jose Araujo Barreiro; Sri Wiyanah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The purpose of this study is to increase English vocabulary using visual mnemonic techniques for seventh graders of junior high school. Several factors inhibited students from having difficulty memorizing vocabulary, lose motivation to memorize vocabulary and easily forgetting the vocabulary they had learned. This inhibiting factor could be overcome by using visual mnemonic techniques to increase students' vocabulary. This study used Classroom Action Research with a sample of 32 students. The research was conducted at SMP N 2 Kasihan, Bantul. Data was collected by observation, interview, pre-test and post-test with instrument field notes, documentation and tests at the end of each study in the entire cycle. Analysis of research data used quantitative and qualitative descriptive data analysis. The results of the study proved that the increase in the percentage of student scores continues to increase. This can be seen in the acquisition of pre-cycle values to the last cycle. The value obtained from the pre-cycle was only 15.93% then increased in the first cycle to 37.38% then in the second cycle there was an increase again. There was a very good increase to 95.75%, with the average student score in the second cycle was 85.31. The increase in student scores in the second cycle, the targeted presentation was 80% and the student KKM was 75. This level of achievement has proven that visual mnemonic technique helped students of SMP N 2 Kasihan, Bantul in increasing students' vocabulary remarkably.